2011
DOI: 10.1021/je2005006
|View full text |Cite
|
Sign up to set email alerts
|

Activity Coefficients of NaClO4 in Aqueous Solution

Abstract: The activity coefficients of NaClO 4 in water were experimentally determined at (288.15, 298.15, and 308.15) K from electromotive force (emf) measurements of the following electrochemical cell without transference containing two ion-selective electrodes (ISEs): Na-ISE|NaClO 4 (m)|ClO 4 -ISE. The molality m varied between about (0.02 and 12) mol 3 kg À1 . The determination of E 0 *, which is necessary to calculate the activity coefficients, was carried out following a method similar to that of Hitchcock, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 25 publications
(40 reference statements)
2
16
0
Order By: Relevance
“…NaClO 4 was chosen because it is an inert electrolyte: it exhibits practically no complexation with metals present in the aqueous form and the sorption of ClO 4 − on oxide surfaces is minimal. 39,40 Similar results were reported by Guo 41 who found that the sorption of U(VI) on goethite was insensitive to the fluctuation of ionic strength, adjusted with NaCl.…”
Section: Effect Of Ionic Strength On U(vi) Sorptionsupporting
confidence: 81%
See 1 more Smart Citation
“…NaClO 4 was chosen because it is an inert electrolyte: it exhibits practically no complexation with metals present in the aqueous form and the sorption of ClO 4 − on oxide surfaces is minimal. 39,40 Similar results were reported by Guo 41 who found that the sorption of U(VI) on goethite was insensitive to the fluctuation of ionic strength, adjusted with NaCl.…”
Section: Effect Of Ionic Strength On U(vi) Sorptionsupporting
confidence: 81%
“…The removal of U(VI) by SRS sediment remained unaffected when ionic strength was adjusted with the addition of NaClO 4 , implying that U(VI) removal under the conditions studied may be mainly attributed to the formation of inner‐sphere complexes. NaClO 4 was chosen because it is an inert electrolyte: it exhibits practically no complexation with metals present in the aqueous form and the sorption of ClO 4 − on oxide surfaces is minimal . Similar results were reported by Guo who found that the sorption of U(VI) on goethite was insensitive to the fluctuation of ionic strength, adjusted with NaCl.…”
Section: Resultssupporting
confidence: 52%
“…electrolyte is higher than in diluted 1 m electrolyte, according to a previous report. 29 On the NMHCF cathode side, two pairs of ox./red. peaks were observed the first peak at 0.64/0.51 V derived from Fe , and a very small third lone peak at 1.49 V derived from the O 2 evolution.…”
Section: Cathode Propertiesmentioning
confidence: 99%
“…As a result, the equilibrium voltage for watersplitting is decreased from its standard value of 1.23 V predicted by thermodynamics. 13,14 From the kinetic viewpoint for the electron transfer, the presence of dissipative effects associated with the 'activation overpotential' (Butler-Volmer's model) at the interface (e.g., Helmholtz compact layer) pushes the minimum (theoretical) voltage predicted for water-splitting to higher voltages 13 due to the presence of an SBI. In this sense, from the kinetic viewpoint, the overpotential for the charge-transfer (watersplitting) reaction can be increased as a function of the electrolyte concentration due to an increase in the amount of specifically adsorbed ionic species that reduces the water activity at the electrode/electrolyte interface.…”
Section: Introductionmentioning
confidence: 99%